DINAMIKA PERUBAHAN SOSIAL MASYARAKAT NELAYAN DALAM MENINGKATKAN TARAF HIDUP DI KELURAHAN MAFUTUTU KOTA TIDORE KEPULAUAN - Husen, Ishak S. (HOLISTIK, Journal Of Social and Culture, 2014)
The community fishers are justpeople living in parts of the coast and suspending their lives at sea, thatproblems concerning the community fishermen is a problem that ismultidimensional. Hence, to be known to the root cause of the issues of povertyin fishermen. There are several aspects of that to be poor fishermen or thecoastal communities, of them; there is no attention a government that considerthe fishermen. The low of human resources and equipment that is used byfishermen influential on how to catch fish, to restrictions in technologyunderstanding make quality and quantity of catch not been improved. Government programs that areimpartial the community fishermen, in which many policies on poverty reductionfor the fishermen are top down and always make the community fishermen as anobject and not a subject. Several programs that relating to the communityfishermen absolutely necessary, namely a social policy prosper the communityand fisherman 's life. Increasing poverty fishermen inmafututu very associated with various other obstacles between the absence ofpolicy development and application of coastal areas and the community fishermenwho integrated or integrated among the development agents, the lack ofconsistency production quantity ( catch ) results. Besides that the lack ofcapital or investment will certainly complicate fishermen in increasing theeconomic activities of fisheries, and finally very influential on the level ofthe income of the fishermen. Low income fishermen would directly impact on thelevel of social welfare affects fishermen so that their social mobility in thevarious access development.Â Keywords:fisherman, human resources, governmente